AM signals with random modulation parameters and their detection - OZIMEK, E.; KONIECZNY, J. (Archives of Acoustics, 1996)
In this article a method of generating AM signals with randomly changing parameters was discussed. This method involves a mod ulation process in which some selected parameters of the modulation waveform (amplitude or frequency) are subjected to random variation. The result of this process are random changes (independent or simultaneous) in the depth or frequency of the modulation of AM signals. Using this method, it is possible to study the detection and discrimination of signals with parameters varying in time. This paper also presents the results of preliminary psychoacoustic studies related to the random amplitude modulation.